2016
DOI: 10.1293/tox.2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib alleviates oxaliplatin-induced hyperalgesia through inhibition of spinal ERK1/2 signaling

Abstract: Numerous pieces of evidence have revealed that oxaliplatin (OXA) evokes mechanical and cold hypersensitivity. However, the mechanism underlying these bothersome side effects needs to be further investigated. It is well known that cyclooxygenase-2 (COX-2) and extracellular signal-regulated kinases (ERK1/2) signaling play crucial roles in several pain states. Our previous data showed that Akt2 in the dorsal root ganglion (DRG) participated in the regulation of OXA-induced neuropathic pain. But it is still unclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…In line with our previous findings 22 , we demonstrated that CXCR1/2 inhibition by DF2726A is effective in reducing p-STAT3, p-FAK and PI3K/p-cortactin activation induced by both taxane and platinum agents, by modulating pivotal markers of chemotherapy-associated neurotoxicity. The activation of COX2 and ERK1/2 pathways can further contribute to cellular damage and neuropathic pain 20,28,29 . Oxaliplatin treatment was reported to induce peripheral neuropathy by triggering the COX2 and p-ERK1/2 cascade pathways 20,28,30 .…”
Section: Discussionmentioning
confidence: 99%
“…In line with our previous findings 22 , we demonstrated that CXCR1/2 inhibition by DF2726A is effective in reducing p-STAT3, p-FAK and PI3K/p-cortactin activation induced by both taxane and platinum agents, by modulating pivotal markers of chemotherapy-associated neurotoxicity. The activation of COX2 and ERK1/2 pathways can further contribute to cellular damage and neuropathic pain 20,28,29 . Oxaliplatin treatment was reported to induce peripheral neuropathy by triggering the COX2 and p-ERK1/2 cascade pathways 20,28,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Meloxicam a selective COX‐2 inhibitor diminishes allodynia in diabetic animals [Kimura and Kontani, ; Bermudez‐Ocana et al, ]. Celecoxib also reduced oxaliplatin‐induced neuropathic pain in mice via inhibition of PI3K/Akt2 in dorsal root ganglion and ERK1/2 pathways in the spinal cord [Chen et al, ; Jiang et al, ]. The antihyperalgesic and antiallodynic activity of celecoxib in diabetic and non‐diabetic rats, is mediated by the opioid system [Rezende et al, ; Juarez‐Rojop et al, ] while celecoxib activates Kv7/MK + channels [Mi et al, ], blocks Na + and L‐type Ca 2+ channels [Park et al, ; Zhang et al, ] and activates cannabinoid‐1 receptors [Rezende et al, ] indicating that celecoxib plays an important role in attenuating hyperalgesia and tactile allodynia in diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…The cold pain threshold test was repeated three times over 5-min intervals. The mean latency was used as the result (Chen et al, 2016; Kim et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have suggested that the inflammatory response is also an important factor in CIPN reduction (Boyette-Davis and Dougherty, 2011; Boyette-Davis et al, 2011). Recent studies showed that MAPKs and NF-ÎșB signaling participate in development of OXA- and PTX-induced neuropathy (Li et al, 2015; Chen et al, 2016; Yeo et al, 2016). In addition, a previous study showed increased extracellular signal related kinase (ERK1/2) and p38 signaling in the DRG.…”
Section: Introductionmentioning
confidence: 99%